The Postprandial Glycaemic and Hormonal Responses Following the Ingestion of a Novel, Ready-to-Drink Shot Containing a Low Dose of Whey Protein in Centrally Obese and Lean Adult Males: A Randomised Controlled Trial - Smith, Kieran; Taylor, Guy S.; Allerton, Dean M.; Brunsgaard, Lise Hoej; Bowden Davies, Kelly A.; Stevenson, Emma J.; West, Daniel J. (Frontiers in Endocrinology, 2021)
Purpose Elevated postprandial glycaemia [PPG] increases the risk of cardiometabolic complications in insulin-resistant, centrally obese individuals. Therefore, strategies that improve PPG are of importance for this population. Consuming large doses of whey protein [WP] before meals reduces PPG by delaying gastric emptying and stimulating the secretion of the incretin peptides, glucose-dependent insulinotropic polypeptide [GIP] and glucagon-like peptide 1 [GLP-1]. It is unclear if these effects are observed after smaller amounts of WP and what impact central adiposity has on these gastrointestinal processes. Methods In a randomised-crossover design, 12 lean and 12 centrally obese adult males performed two 240 min mixed-meal tests, 5–10 d apart. After an overnight fast, participants consumed a novel, ready-to-drink WP shot (15 g) or volume-matched water (100 ml; PLA) 10 min before a mixed-nutrient meal. Gastric emptying was estimated by oral acetaminophen absorbance. Interval blood samples were collected to measure glucose, insulin, GIP, GLP-1, and acetaminophen. Results WP reduced PPG area under the curve [AUC0–60] by 13 and 18.2% in the centrally obese and lean cohorts, respectively (both p <0.001). In both groups, the reduction in PPG was accompanied by a two-three-fold increase in GLP-1 and delayed gastric emptying. Despite similar GLP-1 responses during PLA, GLP-1 secretion during the WP trial was 27% lower in centrally obese individuals compared to lean (p = 0.001). In lean participants, WP increased the GLP-1ACTIVE/TOTAL ratio comparative to PLA (p = 0.004), indicative of reduced GLP-1 degradation. Conversely, no treatment effects for GLP-1ACTIVE/TOTAL were seen in obese subjects. Conclusion Pre-meal ingestion of a novel, ready-to-drink WP shot containing just 15 g of dietary protein reduced PPG in lean and centrally obese males. However, an attenuated GLP-1 response to mealtime WP and increased incretin degradation might impact the efficacy of nutritional strategies utilising the actions of GLP-1 to regulate PPG in centrally obese populations. Whether these defects are caused by an individual’s insulin resistance, their obese state, or other obesity-related ailments needs further investigation. Clinical Trial Registration ISRCTN.com, identifier [ISRCTN95281775]. https://www.isrctn.com/.